Ecologia, sazonalidade e resistência a acaricidas de carrapatos em propriedades rurais do Triângulo Mineiro - Rodrigues, Vinicius da Silva (2022)
CHAPTER II, ABSTRACT: The cattle tick Rhipicephalus microplus is widely distributed in tropical and subtropical regions of the world, responsible for high losses to the cattle production. Therefore, knowledge of the biological and ecological aspects of this tick in each region are essential to establish control strategies. The objective of this study was to describe biology and ecology aspects of this tick in the Triângulo Mineiro region. An evaluation of the non-parasitic phase of this tick was carried out for two years under natural conditions in pasture and forest and under controlled laboratory conditions. Additionally an evaluation of the parasitic phase through tick counts on naturally infested Gir x Holstein crossbred heifers, for three consecutive years was conducted. In pasture, the average egg hatching rates ranged from 1% to 99.4%, resulting in 31 to 3678.1 larvae produced per engorged female, the incubation period ranged from 33.9 to 72.4 days and the survival of the larvae ranged from 23.5 days to 111.5 days. In the forest, the average hatching rate was of 15.8% to 99.2%, the number of larvae produced per female was between 587.2 and 3640.8, with an incubation period ranging from 38.3 days to 80.2 days. and larval survival of from 59.5 to 130.5 days. In laboratory, the parameters were more constant with the average hatching rate varying from 89.7% to 99.7%, number of larvae produced per female from 2206.2 to 3338.4, incubation period from 20.6 to 21 .5 days and survival from 81.8 days to 91.0 days. The most favorable environmental conditions for ticks were observed in spring and summer. On the other hand, the period between late May and early September were deleterious to ticks, as shown by the low hatching rates and reduced number of larvae produced per female. The microenvironment in the forest provided some protection to ticks when conditions were adverse, resulting in a higher hatching rate than ticks of the same series in the pasture. Regarding infestation of cattle, five infestation peaks of infestation were observed per year, indicating five generations of ticks per year, reinforced by the the potential number of annual generations of the observations of the non-parasitic phase. Infestation peaks occurred in mid-summer (January), early autumn (March/April), late autumn (May/June), early spring (September) and late spring (November). With the data obtained, an alternative of strategic control is proposed, starting a series of acaricide treatments with the entrance of the first cold front between May and June. The hypothesis to be tested in this proposal is a superior efficacy in the control of ticks by hitting the last generation of ticks on cattle with acaricides and submitting the survivors, females and later their egg masses, to the most inhospitable environment (increasing cold and drought) in an additive, perhaps synergistic, control effect. CHAPTER III, ABSTRACT: The tick Amblyomma sculptum is typical to the Cerrado biome and one of the most aggressive Brazilian species to humans. This species is important for public health because it transmits the Brazilian Spotted Fever agent to humans. Therefore, there is the need to know aspects of the biology of this tick for control purposes. We herein describe and compare aspects of the biology of the non-parasitic phases of A. sculptum under natural and laboratory conditions. Monthly, engorged larvae, nymphs and females were allocated to three different environments, a Brachiaria (Syn. Urochloa) decumbens pasture area, a forested area adjacent to the pasture and a control environment in the laboratory. Under natural conditions, the longest pre-ecdysis periods for engorged larvae and nymphs were associated with the lowest means of environmental temperature and the shortest with increasing environmental temperature. In the hottest time of the year, the pre-oviposition and incubation period were also accelerated in relation to the coldest periods in both natural environments. The average survival of nymphs and adults reached 274.6 days and 491.6 days, respectively, depending on the place and month and allocation of engorged instars in the environment. The forest exerted a buffering effect against extremes of temperature and humidity, best evidenced by the higher hatching rates compared to pasture. In both pasture and forest, behavioral diapause was evident, and the larvae hatched between October and March remained in diapause until late March or early April. The longest average period of diapause observed in this study was of 180.0 days, seen in ticks allocated in the forest. The vertical movement of the infesting larvae was also studies and it was found that they moved towards the top of the stem in the period when the relative humidity of the air was minimum and the temperature at the maximum of the day and the dispersion of these larvae along the surface occurred hours after the start of temperature increase and relative humidity decrease. CHAPTER IV, ABSTRACT: Ticks are one of the biggest constrains for the dairy production in Brazil, especially in taurine herds and their crosses. For adequate control, it is necessary to know the population variables of ticks and parasite species exchange of between hosts in the regions of interest since this can vary from place to place. This study aimed to evaluate the natural infestation by ticks in dairy cattle and horses from six dairy farms in the Triângulo Mineiro region, Minas Gerais, and to evaluate the resistance to commercially available acaricides of the cattle tick, Rhipicephalus microplus. In two of these farms, ticks were collected monthly and in the other four counts were seasonal (every three months). Counts of the Glória Experimental Farm lasted 36 months, with 540 inspections of cattle and 48,185 R. microplus ticks collected. At the Farm of the Instituto Federal do Triângulo Mineiro, 315 cattle inspections were carried out in 21 collections that resulted in 12570 (99.95%) R. microplus and six (0.05%) Amblyomma sculptum. At Joinha Farm, 120 cattle inspections were carried out on eight occasions and 6515 R. microplus were collected. At São Lucas Farm, 95 cattle inspections were carried out, in eight collections, with 9382 (97.8%) R. microplus and 215 (2.2%) A. sculptum collected. At Morro da Mesa Farm, 22 cattle inspections were carried out in five assessments, with 1293 (99.5%) R. microplus and 7 (0.5%) A. sculptum collected. At Madrinha Medalha Farm, 13 cattle inspections were carried out in four collections, with 541 (99.6%) R. microplus and 2 (0.4%) A. sculptum collected. The monthly tick counts at the Glória Experimental Farm showed that R. microplus can have up to five annual peaks of infestation in the Triângulo Mineiro region. Resistance of the tick R. microplus was detected to three of the five acaricide products tested and, exclusively, at Joinha Farm, to all products tested. This high resistance observed in the Joinha Farm was associated with the constant use of acaricides. In five of the farms, 133 equine inspections were carried out and three species of ticks were found, Dermacentor nitens, A. sculptum and R. microplus. In Glória Experimental Farm, only R. microplus ticks were found, in the Farm of the Federal Institute of the Triângulo Mineiro R. microplus and A. sculptum. On the remaining farm the three tick species were found. In general, equine tick infestations were very low. Infestations by A. sculptum in cattle and horses were characterized by the seasonal occurrence of different stages, with larvae in autumn, nymphs in autumn and winter and adults in spring and summer.